Effect of Pre-Treatment with Sodium Chloride/Sulfuric Acid on the Bornite Concentrate Leaching in Chloride Medium - Navarro-Donoso, P; Vargas-Riquelme, C; Gómez-Barrena, M (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
In this work, the effect of the pre-treatment of bornite concentrate with a sodium chloride– sulfuric acid mixture prior to leaching with chloride solutions was evaluated. The influence of the dosage of NaCl and the resting time in the copper solution was evaluated. The solid residues of the pre-treatment were characterized by XRD to evaluate the changes that took place in the bornite. The experimental results show that as the sitting time and the amount of sodium chloride added are increased, the dissolution of the sulfide species also increased. The pre-treatment affects Cu preferentially because it has greater mobility than iron in the bornite crystal lattice. The pretreatment promotes the formation of soluble Cu and Fe species. The efficiency of the pre-treatment depends largely on the formation of hydrochloric acid in the mixture at the particle level, due to the ease with which it diffuses through the bornite particles, achieving greater penetration of the pretreatment. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.